Analysis of Factors Affecting Work Life Balance in Millennial Students - Ani Muttaqiyathun; Ema Nurmaya (Urecol Journal. Part B: Economics and Business, 2021)
The purpose of this study was to determine the factors that affect the balance of work and school life. The population in this study were Postgraduate students at Ahmad Dahlan University, Yogyakarta. Determination of the sample using purposive sampling technique. The data collection method uses a questionnaire that has been tested for validity and reliability. While the analytical tool used is a partial and simultaneous regression test with the help of SPSS. The results of this study conclude that work demands, working hours, overtime work, work demands, parental status, family size, supervisor support and work autonomy simultaneously have a significant effect on student work-life balance. Partially, job demands, working hours, parental status, family size and support from supervisors have no effect on work-life balance. Meanwhile, overtime work, family demands and work autonomy have a significant effect on the work-life balance of students. This research will be useful for candidates and students who integrate work and school for the success of their studies, for policy makers, namely managers of colleges and workplace institutions and also useful for future researchers who are expected to follow up on the results of this study